Serum vitamin B12 and homocysteine levels in type 2 diabetes patients on metformin - Lala, Kunal; Lala, Divya; Duggad, Saurabh (International Journal of Advances in Medicine, 2020)
Background: Metformin is reported to induce vitamin B12 deficiency, however India data is limited. The present study was conducted to assess the vitamin B12 and homocysteine levels among type 2 diabetes mellitus patients taking metformin. Methods: The present observational study included 60 patients with diabetes mellitus, 30 patients on metformin therapy (at least 6 months) and 30 patients not on metformin use. Laboratory investigations were sent for vitamin B12, homocysteine and HbA1c. Results: Mean vitamin B12 level was 159.67±95.73 and 510.73±206.18 pmol/l in the metformin and non-metformin group respectively (p value <0.001). Serum homocysteine levels were found to significantly higher in the metformin group as compared to non-metformin group (17.39±4.97 vs 14.43±2.43 µmol/l, p value <0.01). Folate levels were similar in the two study groups (22.71±3.67 vs 27.54±2.83 mmol/L). Haemoglobin A1c levels were significantly higher in the metformin group as compared to non-metformin group (7.85±0.97 vs 7.25±0.80 respectively). Triglycerides, high density lipoprotein and total cholesterol levels were found to be similar between the two study groups. However, low density lipoproteins were significantly higher in the metformin group as compared to the non-metformin group (3.7±0.92 vs 3.4±0.86 mmol/l). Conclusions: Our results show metformin use in type 2 diabetes mellitus patients was associated with significantly lower vitamin B12 levels and significantly high homocysteine levels.